Concept Of The Self (Ego) Exemplified In “The Secrets Of The Self” (Asrar-I-Khudi) Of Iqbal - Muzafar, Asma (International Journal of Psychosocial Rehabilitation, 2023)
The word ‘Ego’ is called ‘Self’. In Persian this ego and self means ‘khudi’. Khudi is not an Islamic word, nor derived from Islamic philosophy. For Iqbal, it is like a mantra of action for any human being or nation to succeed. Iqbal has very much belief on one’s ego and self or we can say Khudi. He believes in action and continous struggle. Khudi is like a universal message not only for Indians but also for the human beings of the whole world.Iqbal stopped considering himself a poet to his mind, he became a messenger who used his poetry to awaken humanity to know that why they are in this world, he used his philosophy to get people understand that why God created them. In order to do this, he made the concept of Khudi, a unique and complete conception of personality.